The immunomodulatory role of withania somnifera (L.) dunal in inflammatory diseases - Alanazi, Hamad H.; Elfaki, Elyasa (Frontiers in Pharmacology, 2023)
Withania somnifera (L.) Dunal (Solanaceae) (also known as Ashwagandha) is a botanical drug that has been used for centuries to treat many chronic diseases like high blood pressure, arthritis, diabetes, Alzheimer’s disease, and depression. As many botanical drugs, w. Somnifera possesses anti-inflammatory, antioxidant, anticarinogenic, anti-diabetic, and anti-asthmatic properties. W. somnifera is often compared to the ginseng plant due to its ability to reduce stress, improve cognitive functions (e.g., memory), and promote a healthy immune system. It promotes immunomodulatory effects whose function is to balance the humoral and cellular responses of the adaptive immune system. The therapeutic effect of w. Somnifera is attributed to active ingredients like alkaloids, steroidal lactones (such as withanolides, withaferins), and steroidal saponins. Although w. Somnifera is safe and highly recommended for treating various diseases, the current knowledge and understanding of its operational mechanisms are limited. One of the proposed mechanisms states that w. Somnifera promotes cellular-mediated immunity or initiates chemical interactions that contribute to therapeutic effects. Withania somnifera has been shown to play a significant role in immunological diseases by modulating several cytokines, increasing T-cell proliferation and enhancing macrophages functions. In this review, we will discuss the latest therapeutic effects of w. Somnifera on a number of diseases through modulating immunological markers and which specific components of w. Somnifera induce these therapeutic activities. We will also focus on the chemical properties in w. Somnifera components and their immunomodulatory role in type 2 allergic diseases where type 2 inflammation is highly imbalanced.